Effects of Three Biochars as Adsorbents on Soils Adsorbing Ammonium Nitrogen in Biogas Slurry. (16th July 2017) - Wang, Li-Li; Wu, Jing; Wang, Zhong-Jiang; Li, Wen-Zhe; Zhang, Ke
Abstract : The increasing concern of biogas slurry disposal and nitrogen loss in soils has brought back the interest in using biochar as an adsorbent of biogas slurry in soils. Three types of biochars, commercial activated carbon, pyrolysis productions derived from rice husk, and nut shell, were added as adsorbents in two types of soils (sandy and loamy) at solid weight ratio of 5%, 10%, 15%, and 20% to investigate the effects of biochars on soils adsorbing ammonium nitrogen (N H 4 + -N) in biogas slurry using oscillation method. There was no difference of N H 4 + -N adsorbability for sand soil and loamy soil. The N H 4 + -N adsorption capacity of soils increased as the additive biochars increased from 0 to 20%. The smaller particle size of biochars led to the shorter stable adsorption time and the better N H 4 + -N adsorption capacity. Commercial activated carbon showed the best N H 4 + -N adsorption capacity in biogas slurry, followed by the nut shell carbon. The rice husk carbon was the worst. The results in this study provide a feasible and cost-effective assessment method of biochars for increasing the N H 4 + -N adsorption capacity of soils in biogas slurry, as well as good insight into effects of different biochars on improving N H 4 + -N adsorption capacity of soils.